Parmalim Religious Community's Interest in Sharia Bank: Parmalim Religious Community's Understanding of Interest - Wahyi Busyro; Loura Yuniarti (Studia Economica : Jurnal Ekonomi Islam, 2025)
Indonesia has diverse cultures and religions. Religious diversity officially recognized by the government is Islam, Protestant Christianity, Catholicism, Buddhism, Hinduism, and Confucianism. Interest, which is compensation, is offered by the bank. This ban on bank interest practices is not only prohibited by Islam, but also by other religions. Teach Parmalim religion that doing ipubbaani or making money or goods is considered illegal or forbidden. This research aims to examine how Parmalim religious people understand bank interest and interest in Sharia banks. This research methodology is quantitative which has a population of 150 family heads (KK) located in the city of Pekanbaru. The sample used by 83 respondents using Isaac and Michael's sample formula. This data analysis uses a simple linear regression analysis conducted with the SPSS version 24 application. This research uses understanding as variable X and interest as variable Y The findings of this study show that Parmalim's understanding of variable interest has a significant and positive effect on their interest in Sharia banking. This is demonstrated by a count value (2.319) exceeding the t table (1.990) and a significant value less than 0.05. The results of the R Square test were obtained by a determination coefficient of R2 of 0.62, which showed that the understanding of the interest of Parmalim religious people had an effect of 6.2% on the interest of variable Sharia banking